Towards an Analysis of Efficiency in Research, The Case of Colombian Universities (2019)
(Eng) The aim of this paper is to study the empirical evidence of common growth patterns in total publications by year and the scaling exponents (β) associated with this growth behavior. Furthermore, research activities seem to show increasing returns to scale, and the research networks related to these knowledge generation activities appear to show economies of scale. This paper discusses whether the behavior of efficiency Colombian university institutions resemble the behavior of living organisms. Thus, the efficiency name as total publications by sizes institution, is associated to the scaling coefficients. In addition, this work provides the building blocks for a quantitative model, in which, the observed scalability emerge from the capacity to attract Ph.D. students or create new links to carried out research activities in networks.